Gesellschaftlicher Aufbruch, reale Utopien und die Arbeit am Sozialen - Böhnisch, Lothar; Otto, Hans-Uwe; Staub-Bernascoin, Silvia; Seibel, Marc-Ansgar; Arnold, Patricia; Kühne, Klaus; Gruber, Sabine; Lorenz, Walter; Dimiter Hoffmann, Martin; Litz, Markus; Kantowicz, Ewa; J. Friesenhahn, Günter; et al. (bu,press, 2021)
People around the world recollect socially responsible and desirable values, new forms of living and coexistence as well as eco-social economic activities. This volume is dedicated to these real utopias –positive ideas aiming at a better future and practical approaches combining notions of a more livable society with concrete practical implementations.